الأسباب الاجتماعية لظاهرة العنف المدرسي وعلاقتها ببعض المتغيرات "دراسة ميدانية في مرحلة التعليم الأساسي بمدارس مدينة اللاذقية" - طوالو نادين مصطفى (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث إلى تعرف الأسباب الاجتماعية التي تؤدي إلى حدوث ظاهرة العنف المدرسي, ودراسة الفروق بين المعلمين في مرحلة التعليم الأساسي في تحديد الأسباب الاجتماعية للعنف المدرسي تبعاً لمتغيرات (الجنس, المؤهل التربوي, مكان الإقامة). ولتحقيق أهداف البحث تمّ بناء استبانة وتوزيعها على (348) معلم ومعلمة في مرحلة التعليم الأساسي بمدينة اللاذقية, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج الآتية: 1- تعد التنشئة الأسرية غير السوية, والمستوى الاقتصادي المتدني للأسرة, والوضع الاجتماعي المتردي للأسرة, وجماعة الرفاق السيئة, والبيئة المدرسية غير المناسبة من الأسباب الاجتماعية التي تساهم في ظهور العنف المدرسي لدى تلاميذ التعليم الأساسي في مدينة اللاذقية كما يرى معلمو هذه المرحلة. 2- لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات أفراد العينة في الأسباب الاجتماعية للعنف المدرسي تبعاً لمتغيري الجنس ومكان إقامتهم, وبالتالي فإن المعلمين على اختلاف جنسهم ومكان إقامتهم يرون أن الأسباب الاجتماعية للعنف المدرسي تتمثل بـ (التنشئة الأسرية غير السوية, المستوى الاقتصادي المتدني للأسرة, جماعة الرفاق السيئة, الوضع الاجتماعي المتردي للأسرة, انخفاض المستوى التعليمي للوالدين, البيئة المدرسية غير المناسبة). 3- توجد فروق ذات دلالة إحصائية بين متوسطات درجات أفراد العينة في الأسباب الاجتماعية للعنف المدرسي تبعاً لمتغير وجود مؤهل تربوي, وهذه الفروق لصالح المعلمين الذين يحملون مؤهل علمي تربوي, وبالتالي فإن المعلمين الذين يحملون مؤهل علمي تربوي أقدر على تحديد الأسباب الاجتماعية التي تؤدي إلى ظاهرة العنف المدرسي. The research aims to identify the social causes that give rise to the phenomenon of school violence, and study the differences between teachers in the basic education stage in determining the social causes of school violence due to the variables (gender, educational qualification, place of residence). To achieve the objectives of the research, a questionnaire was built and distributed to (348) teachers in basic education in Latakia. After studying and analyzing, we reached the following results: The family abnormal upbringing, low economic level for the family, deteriorating social status for the family, the community of bad comrades, and the school environment is appropriate social causes that contribute to the emergence of school violence with students of basic education in the city of Latakia as seen by the gurus of this stage. There are no statistically significant differences between the mean scores of the respondents in the social causes of school violence depending on variables sex and place of residence, so the teachers of different gender and place of residence believe that the social causes of violence school is (family abnormal upbringing, low economic level for the family, group bad comrades, deteriorating social situation of the family, the low educational level of the parents, the unfavorable school environment). There are statistically significant differences between the mean scores of the respondents in the social causes of school violence depending on the variable and a qualified educational, and these differences for the benefit of teachers who have a high level of educational, so the teachers who have a higher educational level are better able to identify the causes of social reasons which lead to the phenomenon of school violence.